Early motor evoked potentials in acute stroke: adjunctive measure to MRI for assessment of prognosis in acute stroke within 6 hours - Wöhrle, Johannes C.; Behrens, Stephan; Mielke, Orell; Hennerici, Michael G. (Cerebrovascular diseases, 2004)
BACKGROUND: In acute stroke, a magnetic resonance (MR) perfusion-weighted imaging (PWI) and diffusion-weighted imaging (DWI) mismatch (PWI>DWI mismatch) may indicate tissue at risk for infarction and poor prognosis. However, different to early enthusiasm about this surrogate marker, its validity has shown several drawbacks in individual patients. Rather than relying on imaging, we evaluated motor evoked potentials (MEP) as a measure of cerebral function in the acute stroke setting. - METHODS: Thirteen patients with acute hemiparetic stroke underwent time to peak PWI and DWI within 6 h after onset as well as recordings of early MEP of first dorsal interosseous muscles. Outcome was assessed by the Unified Neurological Stroke Scale and Barthel Index at day 42. - RESULTS: Of 8 patients with PWI>DWI mismatch, 4 patients with normal MEP had a good clinical outcome and 4 patients with absent or pathological MEP had an unfavourable outcome (p < 0.05, Fisher's exact test). In all patients without PWI>DWI mismatch, MEP findings predicted clinical outcome. Normal MEP at day 0--but not PWI/DWI findings--significantly correlated with a good clinical outcome. - CONCLUSIONS: Early MEP recordings in acute stroke patients provide valid prognostic information; they may become more useful for specific treatment decisions than presently available MRI surrogate parameters.